Interaction of heavy chain binding protein (BiP/GRP78) with adenine nucleotides. - Kassenbrock, C K (1989)
Immunoglobulin heavy chain binding protein (BiP/GRP78) is a resident endoplasmic reticulum protein that binds tightly to a number of incompletely assembled or aberrant proteins. BiP also binds ATP and can be purified by ATP affinity chromatography. Here we show that an ATPase activity co-purifies with BiP prepared from canine pancreas. The BiP-associated ATPase has a high affinity for ATP but a low turnover number, suggesting a regulatory, rather than an enzymatic role. We also show that submicromolar levels of ATP or ADP decrease the rate of adsorption of [125I]BiP to nitrocellulose filters coated with protein or non-ionic detergents. In contrast, micromolar levels of AMP increase the rate of adsorption. Furthermore, ATP and ADP decrease the susceptibility of BiP to proteolytic degradation, whereas AMP was found to enhance degradation slightly. Adenine nucleotides may therefore induce or stabilize different conformations of BiP even when ATP hydrolysis does not occur.